Advances in group processes. Vol. 27 - Thye, Shane R.; Lawler, Edward J. (Advances in group processes., 2010)
This volume brings together a collection of papers that examine a range of social psychological and group related phenomena, including original research articles, new theoretical developments, and general reviews of select topics in the group processes literature. Topics examined include how network structures affect comparisons process and the distribution of power, and the emergence of strong power in complex networks. One chapter uses social exchange theory to understand the seeds of corruption, and another asks how social exchange theory might be used to understand multiplex relations.The volume also questions longstanding assumptions in the group processes literature, such as trust as an expressive rather than instrumental act and whether group reflection has any empirical impact on group performance.One contribution links status characteristics theory with social influence network theory and another seeks to understand how racial misclassification impacts mental and physical health outcomes. A final chapter distinguishes between diverse effects of individualism in producing independence or competition, and traces the impact of these forces on group creativity.